1990
DOI: 10.1007/bf01771453
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative active specific immunization in curatively resected colorectal cancer patients with a virus-modified autologous tumor cell vaccine

Abstract: Active specific immunotherapy was performed in a phase I study in 20 colorectal cancer patients after surgical resection of the tumor. An autologous tumor cell vaccine surface modified by Newcastle disease virus (NDV) was used, which showed the following characteristics. After mechanical and enzymatic dissociation of the tumor tissue an average of 5 x 10(7) cells/g tissue was obtained. According to trypan blue dye exclusion assay the average viability was 72%. Following irradiation (200 Gy) the inactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…In further experiments we could show that this protective effect was specific in that PEC against Eb tumour cells that express a different tumour-associated transplantation antigen did not protect against ESb cells. A detailed understanding of immune mechanisms in metastatic animal tumour models is an important prerequisite for designing new protocols of immunotherapy [14,18,30,35].…”
Section: Discussionmentioning
confidence: 99%
“…In further experiments we could show that this protective effect was specific in that PEC against Eb tumour cells that express a different tumour-associated transplantation antigen did not protect against ESb cells. A detailed understanding of immune mechanisms in metastatic animal tumour models is an important prerequisite for designing new protocols of immunotherapy [14,18,30,35].…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine was prepared as previously described in detail [2,13]. Briefly, fresh tumor specimens were dissociated mechanically and enzymatically by DNAse and collagenase.…”
Section: Follow-upmentioning
confidence: 99%
“…We showed in an animal tumor model that the concept of active specific immunotherapy (ASI) using autologous tumor cells modified by Newcastle disease virus (NDV) is a promising strategy to treat microscopic tumor foci [4,19]. In a clinical phase I study we transferred this concept to human colorectal cancer and developed a practical and standardized vaccination protocol [2,13]. In this phase II trial we investigated whether ASI influences (a) the immune response measured by a delayed-type hypersensitivity (DTH) skin reaction to autologous tumor cells and (b) the clinical outcome of patients who underwent liver resection from metastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Sterility and other quality controls were included [31]. Results from phase I and II studies have been reported [20,31,32], The first evaluation of clinical response to adjuvant ASI treatment with autologous tumor cell vaccines modified by NDV infection (ATV-NDV) was done in colorectal cancer patients following resection of liver métastasés [33], In this high-risk group of patients, adjuvant chemotherapy has only limited success and 70-80% relapse within 5 years from the outgrowth of micro metastasis not detectable at the time of liver resection. The objective of the study was to investigate w'hether ASI influ ences (a) the immune response to autologous tumor cells and (b) the recurrence-free and overall survival of vaccinated pati ents compared with nonvaccinated matched controls.…”
Section: Clinical Studiesmentioning
confidence: 99%